Members of the microalgae family Scenedesmaceae feature individual N-glycan patterns, a shared Man5GlcNAc2 isomer and core alpha1,6-fucosylation - Réka Tünde Mócsai; Johannes Stadlmann; Friedrich Altmann (Algal Research, 2026)

Pseudomonas syringae DC3000 infection increases glucosylated N-glycans in Arabidopsis thaliana - Gernot Beihammer; Andrea Romero-Pérez; Daniel Maresch; Rudolf Figl; Réka Mócsai; Clemens Grünwald-Gruber; Friedrich Altmann; Els J. M. Van Damme; Richard Strasser (Glycoconjugate Journal, 2023)
Studying the interaction between the hemibiotrophic bacterium Pseudomonas syringae pv. tomato DC3000 and Arabidopsis thaliana has shed light onto the various forms of mechanisms plants use to defend themselves against pathogen attack. While a lot of emphasis has been put on investigating changes in protein expression in infected plants, only little information is available on the effect infection plays on the plants N-glycan composition. To close this gap in knowledge, total N-glycans were enriched from P. syringae DC3000-infected and mock treated Arabidopsis seedlings and analyzed via MALDI-TOF–MS. Additionally, fluorescently labelled N-glycans were quantified via HPLC-FLD. N-glycans from infected plants were overall less processed and displayed increased amounts of oligomannosidic N-glycans. As multiple peaks for certain oligomannosidic glycoforms were detected upon separation via liquid chromatography, a porous graphitic carbon (PGC)-analysis was conducted to separate individual N-glycan isomers. Indeed, multiple different N-glycan isomers with masses of two N-acetylhexosamine residues plus 8, 9 or 10 hexoses were detected in the infected plants which were absent in the mock controls. Treatment with jack bean α-mannosidase resulted in incomplete removal of hexoses from these N-glycans, indicating the presence of glucose residues. This hints at the accumulation of misfolded glycoproteins in the infected plants, likely because of endoplasmic reticulum (ER) stress. In addition, poly-hexose structures susceptible to α-amylase treatment were found in the DC3000-infected plants, indicating alterations in starch metabolism due to the infection process.

Thorsmoerkia curvula gen. et spec. nov. (Trebouxiophyceae, Chlorophyta), a semi-terrestrial microalga from Iceland exhibits high levels of unsaturated fatty acids - Cecilia Nicoletti; Lenka Procházková; Linda Nedbalová; Réka Mócsai; Friedrich Altmann; Andreas Holzinger; Daniel Remias (Journal of Applied Phycology, 2021)
A terrestrial green alga was isolated at Iceland, and the strain (SAG 2627) was described for its morphology and phylogenetic position and tested for biotechnological capabilities. Cells had a distinctly curved, crescent shape with conical poles and a single parietal chloroplast. Phylogenetic analyses of 18S rDNA and rbc L markers placed the strain into the Trebouxiophyceae (Chlorophyta). The alga turned out to belong to an independent lineage without an obvious sister group within the Trebouxiophyceae. Based on morphological and phylogenetic data, the strain was described as a new genus and species, Thorsmoerkia curvula gen. et sp. nov. Biomass was generated in column reactors and subsequently screened for promising metabolites. Growth was optimized by pH-regulated, episodic CO 2 supplement during the logarithmic growth-phase, and half of the biomass was thereafter exposed to nitrogen and phosphate depletion. The biomass yield reached up to 53.5 mg L −1 day −1 . Fatty acid (FA) production peaked at 24 mg L −1 day −1 and up to 83% of all FAs were unsaturated. At the end of the log phase, approximately 45% of dry mass were lipids, including eicosapentaenoic acid. Carotenoid production reached up to 2.94 mg L −1 day −1 but it was halted during the stress phase. The N-linked glycans of glycoproteins were assessed to reveal chemotaxonomic patterns. The study demonstrated that new microalgae can be found at Iceland, potentially suitable for applied purposes. The advantage of T. curvula is its robustness and that significant amounts of lipids are already accumulated during log phase, making a subsequent stress exposure dispensable.

Seed-produced anti-globulin VHH-Fc antibodies retrieve globulin precursors in the insoluble fraction and modulate the Arabidopsis thaliana seed subcellular morphology - Thomas De Meyer; Elsa Arcalis; Stanislav Melnik; Katrien Maleux; Jonah Nolf; Friedrich Altmann; Ann Depicker; Eva Stöger (Plant Molecular Biology, 2020)

Detailed characterization of the O-linked glycosylation of the neuropilin-1 c/MAM-domain - Markus Windwarder; Tamas Yelland; Snezana Djordjevic; Friedrich Altmann (Glycoconjugate Journal, 2016)

UDP-N-acetyl-α-D-galactosamine:polypeptide N-acetylgalactosaminyl-transferase from the snail Biomphalaria glabrata – substrate specificity and preference of glycosylation sites - Christopher Taus; Markus Windwarder; Friedrich Altmann; Reingard Grabherr; Erika Staudacher (Glycoconjugate Journal, 2014)

Protein O-glucosylation in Lactobacillus buchneri - Julia Anzengruber; Martin Pabst; Laura Neumann; Gerhard Sekot; Stefan Heinl; Reingard Grabherr; Friedrich Altmann; Paul Messner; Christina Schäffer (Glycoconjugate Journal, 2014)

Plant species and organ influence the structure and subcellular localization of recombinant glycoproteins - Elsa Arcalis; Johannes Stadlmann; Thomas Rademacher; Sylvain Marcel; Markus Sack; Friedrich Altmann; Eva Stoger (Plant Molecular Biology, 2013)

O-Glycosylation of snails - Herwig Stepan; Martin Pabst; Friedrich Altmann; Hildegard Geyer; Rudolf Geyer; Erika Staudacher (Glycoconjugate Journal, 2012)

The two endo-β-N-acetylglucosaminidase genes from Arabidopsis thaliana encode cytoplasmic enzymes controlling free N-glycan levels - Richard M. Fischl; Johannes Stadlmann; Josephine Grass; Friedrich Altmann; Renaud Léonard (Plant Molecular Biology, 2011)

Functional specialization of Medicago truncatula leaves and seeds does not affect the subcellular localization of a recombinant protein - Rita Abranches; Elsa Arcalis; Sylvain Marcel; Friedrich Altmann; Marina Ribeiro-Pedro; Julian Rodriguez; Eva Stoger (Planta, 2008)

Sialic acid concentrations in plants are in the range of inadvertent contamination - Reinhard Zeleny; Daniel Kolarich; Richard Strasser; Friedrich Altmann (Planta, 2006)

Unaltered complex N-glycan profiles in Nicotiana benthamiana despite drastic reduction of β1,2-N-acetylglucosaminyltransferase I activity - Richard Strasser; Friedrich Altmann; Josef Glössl; Herta Steinkellner (Glycoconjugate Journal, 2004)

A genetic and structural analysis of the -glycosylation capabilities - Renaud Lonard; Daniel Kolarich; Katharina Paschinger; Friedrich Altmann; Iain Wilson (Plant Molecular Biology, 2004)

Insect cells as hosts for the expression of recombinant glycoproteins - Friedrich Altmann; Erika Staudacher; Iain B.H. Wilson; Leopold März (Glycoconjugate Journal, 1999)

Structural analysis of N-glycans from allergenic grass, ragweed and tree pollens: Core α1,3-linked fucose and xylose present in all pollens examined - Iain B. H. Wilson; Friedrich Altmann (Glycoconjugate Journal, 1998)

Concanavalin A binding and endoglycosidase D resistance of beta1,2-xylosylated and alpha 1,3-fucosylated plant and insect oligosaccharides - Iain B.H Wilson; Friedrich Altmann (Glycoconjugate Journal, 1998)

HPLC method for the determination of Fuc to Asn-linked GlcNAc fucosyltransferases - Andreas Roitinger; Harald Leiter; Erika Staudacher; Friedrich Altmann (Glycoconjugate Journal, 1998)

Structures of the N-linked carbohydrate of ascorbic acid oxidase from zucchini - Friedrich Altmann (Glycoconjugate Journal, 1998)

More than silk and honey–or, can insect cells serve in the production of therapeutic glycoproteins? - Friedrich Altmann (Glycoconjugate Journal, 1997)

The α- d -mannan core of a complex cell-wall heteroglycan of Trichoderma reesei is responsible for β-glucosidase activation - J. Rath; Robert Messner; Paul Kosma; Friedrich Altmann; Leopold März; Christian P. Kubicek (Archives of Microbiology, 1995)

The α-d-mannan core of a complex cell-wall heteroglycan ofTrichoderma reesei is responsible for β-glucosidase activation - Johannes Rath; Robert Messner; Paul Kosma; Friedrich Altmann; Leopold März; Christian P. Kubicek (Archives of Microbiology, 1995)